Sur une nouvelle stratégie commerciale pour le Canada - Bronsard, Camille (L'Actualité économique)

(untitled) (HEC Montréal, 1976)
AbstractAfter greeting the recent propositions of the E.C.C.'s Report ("Au-delà des frontières") as a potentially useful document to encourage discussions on the efficiency of our institutions, the reviewer recasts them in a first best framework, a second best one and a socio-cultural one. By any standard, these propositions are disappointing: irrealist if their target is a world-wide first best, illogical if aiming at a second best world, countermarches if done to enhance cultural identity. The author concludes by suggesting that the E.C.C. was not exactly conceived to promote such an academic oratorio.